Analisis Faktor-Faktor Penyebab Terjadinya Selisih Jumlah Stock Barang digudang PT. Solo Murni Boyolali Menggunakan Metode 5W+1H dan Fishbone Diagram - Nata Franciska (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This research aims to find out what is the analysis of the factors that cause differences in the amount of stock in PT's warehouse. Solo Murni Boyolali and what strategies the company is implementing to overcome these problems. This research was carried out in the field using observation, interviews and documentation methods involving warehouse supervisors and warehouse employees during the process of receiving, issuing, storing and controlling warehouse stock. The method used to conduct this research is a qualitative method with 5W+1H analysis techniques and fishbone diagram analysis. According to the research results, the factors that cause differences in the amount of stock of goods vary. One of them is that employees are not careful when doing their work and the calculation system is still manual. The strategy that companies must implement to minimize warehouse stock differences is to provide outreach to employees about receiving goods in the warehouse, storing goods in the warehouse, and controlling operational activities